DETERMINANTS OF RURAL WOMEN POULTRY FARMERS’ ACCESS TO AGRICULTURAL INFORMATION IN IMO STATE, NIGERIA: A LOGIT MODEL ANALYSIS - F.C, Anaeto; D.O, Ohajianya; A.O, Ani; A.O, Ani A.O; Njoku E.C, Mathews; O.C, Korie; U.C, Ozor; Nnebene E, Adolph; C.O, Osuagwu (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
The study analyzed the determinants of rural women poultry farmers’ access toagricultural information in Imo State, Nigeria. Data were obtained in 2015 withstructured and validated questionnaire from 201 proportionately and randomlyselected rural women poultry farmers. Data were analyzed using descriptivestatistics (mean and percentage) and inferential statistics (logit model). Resultsshowed that extension contacts, attendance to agricultural extension seminarsand workshops, as well as accessibility of media methods were very poor.Determinants, of rural women poultry farmers’ access to agriculturalinformation were age, education level, frequency of attendance to associations’meetings, farming experience, farm size, attendance to agricultural extensionseminars and workshops, access to credit, and accessibility to media methods.Rural women poultry farmers should be encouraged to participate actively inextension services organized trainings, seminars and workshops to improvetheir access to agricultural information